CoRe dan PaP-eRs Test untuk Mengukur Pedagogical Content Knowledge (PCK) Calon Guru Fisika - Rafiah, Jihan Ariqatur; Winarti, Winarti (Edusainstika: Jurnal Pembelajaran MIPA, 2024)
Teacher is one of the important components in learning activities. A teacher must have good Pedagogical Content Knowledge (PCK) competence. PCK is a combination of teaching knowledge (pedagogic) and knowledge of teaching materials (content). The purpose of this study was to identify the PCK competence of physics teacher candidates using CoRe (Content Represantation) and PaP-eRs (Pedagogical and Professional-experience Repertories) instruments. The method used in this research is a quantitative approach to identify the PCK abilities of prospective physics teachers in the Physics Education study program at UIN Sunan Kalijaga Yogyakarta as measured by two instruments, namely CoRe and PaP-eRs. Based on the results of the research analysis, it can be concluded that in some indicators, prospective physics teachers are still weak in understanding PCK and it is important to make improvements in the selection of appropriate learning strategies. Prospective physics teachers also still experience misconceptions when learning in class, especially in the mteri of effort and energy